Natriuretic Peptides in the Management of Solid Organ Transplantation Associated Acute Kidney Injury: A Systematic Review and Meta-Analysis - Nigwekar, Sagar U.; Kulkarni, Hrishikesh; Thakar, Charuhas V. (International Journal of Nephrology, 2013)
Randomized controlled trials involving natriuretic peptide administration in solid organ transplantation setting have shown inconsistent effects for renal endpoints. We conducted a systematic review and meta-analysis of these trials to ascertain the role of natriuretic peptides in the management of solid organ transplantation associated acute kidney injury (AKI). MEDLINE, EMBASE, and Google scholar were searched independently by two authors for randomized trials evaluating renal effects of natriuretic peptides in solid organ transplantation settings. Two reviewers independently assessed the studies for eligibility and extracted the relevant data. The pooled estimate showed that natriuretic peptide administration is associated with a reduction in AKI requiring dialysis (odds ratio = 0.50 [0.26–0.97]), a statistically nonsignificant trend toward improvement in posttransplant creatinine clearance (weighted mean difference = 5.5 mL/min, [−1.3 to 12.2 mL/min]), and reduction in renal replacement requirement duration (weighted mean difference −44.0 hours, [−60.5 to −27.5 hours]). There were no mortality events and no adverse events related to natriuretic peptides. In conclusion, administration of natriuretic peptides in solid organ transplantation may be associated with significant improvements in renal outcomes. These observations need to be confirmed in an adequately powered, prospective multicenter study.